Training alterations in elite cyclists may cause transient changes in glomerular filtration rate - Touchberry, C. D.; Ernsting, M.; Haff, G.; Kilgre, J. L. (Journal of Sports Science & Medicine, 2004)
Training alterations in elite cyclists may cause transient changes in glomerular filtration rate. To these authors' knowledge, no biochemical investigation of chronic renal function in athletes during a training cycle exists. The purpose of the present archival study was to evaluate the effects of training on homeostatic renal function, evaluated predicted glomerular filtration rate (GFR). Eight male competitive college cyclists (mean ± SD: age: 22.2 ± 3.8 yrs, height: 1.80 ± 0.06 m, mass: 76.6 ± 7.9 kg, and body fat was 7 ± 2%) volunteered to undergo 12 weeks of training, and were required to undergo blood sampling at timed intervals to calculate GFR. Homeostatic GFR was altered significantly during various points in the investigation. Volume and average cycling speed were found to have moderate correlations to alterations in GFR. In addition to these findings, 7 of the 8 subjects had GFR's below normal physiological ranges during some point in the experiment. The duration, intensity, and volume of cycling appear to have an influence on renal function. This influence is pronounced during periods when the athletes are unaccustomed to the training load.